Determinants of FDI in Selected Asian Countries - Aikeda, Aili (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis aims to examine the determinants of foreign direct investment (FDI) in 20 selected Asian countries in the time period of 2013 to 2017 by using panel data model. Fixed and random two types of panel data techniques have used during the analysis for the classical eight determinants of FDI, to see whether they are also relevant in the case of Asian countries. The determinants tested are GDP as representative of the market size, GDP per capita, labor force, inflation as macroeconomic stability, fuel exports as natural resources, domestic credit to private sectors as financial development, trade openness and economic growth rate. The findings show that economic growth, GDP, trade openness and labor force are the significant determinants of FDI in the sample Asian countries. While, GDP per capita, inflation, fuel exports, domestic credit to private sectors have no significant impact on FDI. Based on these results, policy recommendations are put forward to the 20 Asian countries. In order to increase FDI, additional improvements should be made in GDP, labor force, trade openness and economic growth. Keywords: FDI, GDP, GDP per capita, trade openness, fuel exports, labor force, economic growth, inflation, Asian countries

ÖZ: Bu tez, 2013-2017 döneminde seçilen 20 Asya ülkesinde doğrudan yabancı yatırımın (DYY) belirleyicilerini panel veri modelini kullanarak incelemeyi amaçlamaktadır. Analiz sırasında, DYY'nin klasik sekiz belirleyicisinin Asya ülkeleri durumunda da uygun olup olmadıklarını görmek için sabit ve rastgele iki tür panel veri tekniği kullanılmıştır. Test edilen belirleyiciler; pazar büyüklüğünü temsil eden GSYİH, kişi başına GSYİH, işgücü, makroekonomik istikrar enflasyonu, doğal kaynaklar olarak yakıt ihracatı, finansal gelişme olarak özel sektörlere iç kredi, ticaret açıklığı ve ekonomik büyüme oranıdır. Bulgular, ekonomik büyüme, GSYİH, dışa açıklık ve işgücünün, örnek Asya ülkelerinde doğrudan yabancı yatırımın önemli belirleyicileri olduğunu göstermektedir. Kişi başına GSYİH, enflasyon, akaryakıt ihracatı, özel sektöre verilen yurt içi kredilerin doğrudan yabancı yatırımlar üzerinde önemli bir etkisi yoktur. Bu sonuçlara dayanarak, 20 Asya ülkesine politika önerileri sunulmuştur. Doğrudan yabancı yatırımın arttırılması için GSYİH, iş gücü, dışa açıklık ve ekonomik büyüme konularında ilave iyileştirmeler yapılmalıdır. Anahtar kelimeler: DYY, GSYİH, Kişi başına GSYİH, dışa açıklık, akaryakıt ihracatı, işgücü, ekonomik büyüme, enflasyon, Asya ülkeleri
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Co-Supervisor: Prof. Dr. Cem Payaslıoğlu and Supervisor: Prof. Dr. Melek Şule Aker.
Keywords: Business Administration; Marketing Management; Economic Conditions and Development--Asia; Investments, Foreign--Asian Countries; FDI; GDP; GDP per capita; trade openness; fuel exports; labor force; economic growth; inflation; Asian countries